La dynamique de la stratégie nucléaire américaine de contreforce - David, Charles-Philippe (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
This article examines the growth of the American nuclear strategy of counterforce, by investigating three factors which contributed to its successful development in the first Reagan administration. These factors are: first, the excessive worst-case forecasting of policy-makers in dealing with Moscow's military intentions and capabilities ; secondly, the technological hard-sell of the idea that "star wars" defenses in the future might protect the U.S. from a Soviet nuclear attack; and finally, the bureaucratic momentum of military demands for more weapons to satisfy organizational interests and the ideology of offense.